Systematic Evaluation of Patient-Reported Outcome Protocol Content and Reporting in Cancer Trials. (11th April 2019) - Kyte, Derek; Retzer, Ameeta; Ahmed, Khaled; Keeley, Thomas; Armes, Jo; Brown, Julia M; Calman, Lynn; Gavin, Anna; Glaser, Adam W; Greenfield, Diana M; Lanceley, Anne; Taylor, Rachel M; et al.
Abstract: Background: Patient-reported outcomes (PROs) are captured within cancer trials to help future patients and their clinicians make more informed treatment decisions. However, variability in standards of PRO trial design and reporting threaten the validity of these endpoints for application in clinical practice. Methods: We systematically investigated a cohort of randomized controlled cancer trials that included a primary or secondary PRO. For each trial, an evaluation of protocol and reporting quality was undertaken using standard checklists. General patterns of reporting where also explored. Results: Protocols (101 sourced, 44.3%) included a mean (SD) of 10 (4) of 33 (range = 2–19) PRO protocol checklist items. Recommended items frequently omitted included the rationale and objectives underpinning PRO collection and approaches to minimize/address missing PRO data. Of 160 trials with published results, 61 (38.1%, 95% confidence interval = 30.6% to 45.7%) failed to include their PRO findings in any publication (mean 6.43-year follow-up); these trials included 49 568 participants. Although two-thirds of included trials published PRO findings, reporting standards were often inadequate according to international guidelines (mean [SD] inclusion of 3 [3] of 14 [range = 0–11]) CONSORT PRO Extension checklist items). More than one-half of trials publishing PRO results in a secondary publication (12 of 22, 54.5%) took 4 or more years to do so following trial closure, with eight (36.4%) taking 5–8 years and one trial publishing after 14 years. Conclusions: PRO protocol content is frequently inadequate, and nonreporting of PRO findings is widespread, meaning patient-important information may not be available to benefit patients, clinicians, and regulators. Even where PRO data are published, there is often considerable delay and reporting quality is suboptimal. This study presents key recommendations to enhance the likelihood of successful delivery of PROs in the future.